Compounding impact of deforestation on Borneo's climate during El Niño events. (15th July 2020) - Chapman, Sarah; Syktus, Jozef; Trancoso, Ralph; Salazar, Alvaro; Thatcher, Marcus; Watson, James E M; Meijaard, Erik; Sheil, Douglas; Dargusch, Paul; McAlpine, Clive A
Abstract: Both deforestation and El Niño events influence Borneo's climate, but their interaction is not well understood. Borneo's native forest cover decreased by 37.1% between 1980 and 2015 with large areas being replaced by oil palm and a mosaic of plantations and regrowth vegetation. The island is also affected by El Niño events, resulting in severe droughts and fires. Here, we used a high-resolution climate model to simulate and evaluate how deforestation and El Niño episodes interact during the 1980–2016 period. Simulations revealed that deforestation resulted in a warmer and drier climate with the most pronounced changes in the extensively deforested regions of eastern and southern Borneo. Deforestation-linked impacts were more pronounced under El Niño than neutral (non El Niño/La Niña) conditions. Changes in climate mainly corresponded with areas with the most deforestation. There was a significant increase in the frequency of hotter and drier climatic extremes, with the probability distribution of temperature, humidity and aridity shifting from narrow to a broadening distribution. For example, the frequency of 90th percentile of the hot temperatures (defined as average monthly temperatures >28.9 °C) during the dry season increased from 10% for neutral conditions for the 1980 forest cover to 22% for neutral conditions for the 2015 forest cover. For strong El Niño events, the frequency increased from 15.6% to 32.5%. Replacement of intact native forest with oil palm resulted in increased frequency of hot temperatures to 49% for neutral and 74% for El Niño conditions. Hotter and drier conditions are likely to increase tree mortality and forest flammability (and fire-driven deforestation). The continued reduction and fragmentation of Borneo's forests diminishes the ability to moderate regional climate impacted by larger scale and other regional/local human climate forcings.